"Game playing" and "docility": youth justice in question. Issue 3 (1st July 2020) - Creaney, Sean
Abstract : Purpose: The purpose of this paper is to explore young people's experiences of youth justice supervision with particular reference to the efficacy of participatory practices. This paper is based on findings from a study concerning the extent and nature of children's participation in decision-making in youth justice. The paper uses Bourdieu's concept of habitus, as a heuristic/practical device, to investigate children's ability to express agency and shape or influence the content and format of interventions and approaches in youth justice. Design/methodology/approach: The researcher's interest in understanding the perceptions and experiences of youth justice supervision led to the adoption of the qualitative approach and specifically in-depth interviews and participant observations. The researcher interviewed front-line professionals (n = 14), operational managers (n = 6) and children under youth justice supervision (n = 20). This study involved 15 months of fieldwork undertaken between 2016 and 2017 at a youth offending service in England. Findings: Several young people were seeking to exert minimal energy to achieve a type of passive compliance with court order requirements, adopting a "ready-to-conform" mindset. Professionals were concerned that they were also participating in this type of "game playing". Practical implications: A relationship-based practice that is conducive to meaningful participation can help to facilitate positive changes to lifestyles and circumstances. This paper exposes its pivotal role in bolstering children's involvement in supervision, reducing passive compliance and preventing inauthentic transactional arrangements from forming. Originality/value: In spite of the significant interest in the work of Pierre Bourdieu, his "thinking tools" have seldom been used to investigate the experiences, attitudes and behaviours of youth justice professionals and those under youth offending team supervision at.